Increasing temperature decreases the predatory effect of the intertidal shanny Lipophrys pholis on an amphipod prey. Issue 1 (15th November 2017) - South, J.; Welsh, D.; Anton, A.; Sigwart, J. D.; Dick, J. T. A.
Abstract : Interactions between Lipophrys pholis and its amphipod prey Echinogammarus marinus were used to investigate the effect of changing water temperatures, comparing current and predicted mean summer temperatures. Contrary to expectations, predator attack rates significantly decreased with increasing temperature. Handling times were significantly longer at 19° C than at 17 and 15° C and the maximum feeding estimate was significantly lower at 19° C than at 17° C. Functional‐response type changed from a destabilizing type II to the more stabilizing type III with a temperature increase to 19° C. This suggests that a temperature increase can mediate refuge for prey at low densities. Predatory pressure by teleosts may be dampened by a large increase in temperature (here from 15 to 19° C), but a short‐term and smaller temperature increase (to 17° C) may increase destabilizing resource consumption due to high maximum feeding rates; this has implications for the stability of important intertidal ecosystems during warming events.